CORRELATION OF SCROTAL CIRCUMFERENCE, BODY WEIGHT WITH SPERM PRODUCTION OF THE PASUNDAN BULLS: HUBUNGAN LINGKAR SKROTUM, BOBOT BADAN DENGAN PRODUKSI SPERMATOZOA PEJANTAN SAPI PASUNDAN (Jurnal Peternakan Nusantara, 2022)
The study aims to measure the reproductive potential of Pasundan bulls through the relationships between scrotal circumference, body weight with sperm production. Semen was collected twice from five sexually mature Pasundan bulls aged 3-5 years old using an artificial vagina and evaluated macro- and microscopically. Data were analyzed using SPSS 20 with One-Way ANOVA methode and the relationship between variables using Pearson correlation (r). The result showed no differences in the scrotal circumference (25±2.45 cm), body weight (306.08±10.86 kg), volume (3.80±0.58 ml), and spermatozoa concentration (1355.85±6.06×106/ml) in Pasundan bulls. The results showed that scrotal circumference parameters were related to body weight and spermatozoa production (semen volume and spermatozoa concentration) in Pasundan bulls.